KARAKTERISTIK SIFAT FISIKA BATANG KARET NON PRODUKTIF - Kusumawardi, M. Ridho; Hamzah, Faizah; Hamzah, Farida Hanum (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Rubber can be used as a source of wood raw materials for various uses such as wood fanel, pulp and paper products, furniture and other processed wood products. The aim of the research was to get the characteristic part of rubber stem physical of non-productive rubber stem in the base, middle, and of the tree end. The experiment was conducted using experimental method using Completely Randomized Design (CRD) which consisted of three treatments and five replications to obtain 15 experimental units and continued with Duncan's New Multiple Range Test (DNMRT) test at 5% level. The treatments in this study included rubber stem at the base (K1), rubber stem in the middle (K2) and rubber stem at the end (K3). The results of variance analysis showed that the treatment at the base, middle, and rubber stem ends significantly affected the specific gravity of wood produced from rubber stem ranging from 0.779 to 0.606 kg/cm3. Wood water content generated from rubber stem ranged from 5.306 to 7.485%. Shrinkage of radial wood resulting from rubber stem ranged from 4.327 to 5.681%, and the tangential depreciation resulting from the rubber stem ranged from 4.685 to 5.813%. Keywords: rubber stem, physical properties, wood raw materials